Mayo Clinic book of home remedies : what to do for the most common health problems - Hagen, Philip T.; Millman, Martha (Time Home Entertainment, 2010)
A resource that first helps readers discern whether or not a problem can be treated at home, offers information on treating common ailments through natural alternatives, and provides basic instruction in emergency care--